Movers & fakers : an Alphas novel - Harrison, Lisi (Little, Brown and Company, 2010)
At the elite Alpha Academy, where every girl is used to being the best, Charlie's efforts to encourage Allie and Darwin's romance backfire, while Skye finds it increasingly difficult to focus on dance.